ANALISIS MATERIAL SHRINKAGE PADA INDUSTRI PENGOLAHAN KARET MENGGUNAKAN METODE FAILURE MODE AND EFFECT ANALYSIS (FMEA) DAN FAULT TREE ANALYSIS (FTA) - Afdi Nugraha, (2023)
PT. X is a company engaged in the processing of dirty rubber into clean rubber. Based on company data for January 2019-August 2022, PT. X experienced material shrinkage of 1620 tons with an estimated financial loss of 34.3 billion rupiah. Thus, business process improvements need to be carried out in order to minimize material shrinkage at PT. X. The results of FMEA data processing obtained 12 failure factors with 2 critical failure factors in the activity of purchasing raw material (dirty rubber) with a Risk Priority Number of 573.75 and 476, namely inaccurate results of estimation of raw material content (dirty rubber) carried out by the estimation team and the failure of the purchasing team in negotiating with the seller with a total percentage of the Risk Priority Number of 42.3%. This is because the failure has a Risk Priority Number value that is greater than the critical Risk Priority Number value of 206.8 as the lower limit of critical failure. Furthermore, these critical failures were processed using the FTA method to produce 7 intermediate events and 8 basic events (root causes). Proposed improvements are given using the 5W-1H method based on the root cause of the critical cause of material shrinkage at PT. X. From this proposed improvement, it is expected to reduce the amount of material shrinkage that occurs at PT. X of 42.3%